RELATIONSHIPS BETWEEN OSTEOCALCIN LEVEL AND HORMONAL METABOLIC DISORDERS IN TYPE 2 DIABETIC MEN WITH VARIOUS DEGREES OF OBESITY (LITERATURE REVIEW AND OWN RESEARCH) (World Science, 2021)
The bone hormone osteocalcin is formed by osteoblasts and is partially released into the bloodstream during bone resorption, being a biomarker of bone remodeling. Osteocalcin also plays an important role in the endocrine regulation of metabolic and energy processes in the body and in their coordination. Osteocalcin uses a feedback mechanism to regulate insulin secretion, insulin sensitivity of peripheral tissues, and adipokine levels. In general, the secretion of osteocalcin and insulin are important factors in the formation of hormonal-metabolic phenotype, body composition, determination of regional distribution and metabolic activity of both bone and adipose tissue.The aim of this study was to establish the relationship between osteocalcin concentration and hormonal changes in men with type 2 diabetes with and without obesity on the background of involutive changes. Results. 64 men with type 2 diabetes, older than 50 years, were divided into 2 groups by BMI: 1) non-obese, BMI